Increasing antigen presentation on HSV-1-infected cells increases lesion size but does not alter neural infection or latency - Russell, Tiffany A.; Velusamy, Thilaga; Tseng, Yeu-Yang; Tscharke, David C. (Journal of general virology, 2018)
CD8 + T cells have a role in the control of acute herpes simplex virus (HSV) infection and may also be important in the maintenance of latency. In this study we have explored the consequences of boosting the efficacy of CD8 + T cells against HSV by increasing the amount of an MHC I-presented epitope on the surface of infected cells. To do this we used HSVs engineered to express an extra copy of the immunodominant CD8 + T cell epitope in C57Bl/6 mice, namely gB 498 (SSIEFARL). Despite greater presentation of gB 498 on infected cells, CD8 + T cell responses to these viruses in mice were similar to those elicited by a control virus. Further, the expression of extra gB 498 did not significantly alter the extent or stability of latency in our mouse model, and virus loads in skin and sensory ganglia of infected mice were not affected. Surprisingly, mice infected with these viruses developed significantly larger skin lesions than those infected with control viruses and notably, this phenotype was dependent on MHC haplotype. Therefore increasing the visibility of HSV-infected cells to CD8 + T cell attack did not impact neural infection or latency, but rather enhanced pathology in the skin.